LOCAL STUDY ON PERFLUORINATED MATERIALS AND THEIR PRESENCE IN SOME FOODS IN BAGHDAD GOVERNORATE - Al-Attar, Huda; Al-Darwash , Amer (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2026)
The objective of this study is to identify and quantify perfluorinated substances in different ready-to-eat foods found in the local markets of Baghdad Governorate. The emphasis is placed on these substances due to their extensive use in paper and cardboard packaging materials and the consequential health effects. The analysis utilized liquid chromatography coupled with mass spectrometric detection equipped with electrospray ionization. The values recorded for perfluorinated materials in samples of crispy chicken and french fries were (2.41 and 4.94) micrograms, respectively. As for samples of kebab, pizza, and cake, they were (5.14, 5.80 and 7.32) micrograms, respectively, and samples taken from stored ice cream (15-30–45) days recorded (0.23, 0.42 and 2.26) micrograms, respectively. It was found that the percentage of fat and the amount of perfluorinated substances in foods are directly related, and this is clearly evident from the fact that it was not detected in the French Bread samples, and may be due to the low percentage of fat which amounted to 0.86%., compared to the samples that showed positive results.